The Phonological Changes in Semitic Words and Their Impact on Old Testament Aramaic (A Comparative Study) - MUAYAD HUSSEIN MUNSHED, Prof. Dr. (lark, 2025)
Linguists have given a great consideration to the study and analysis of letters, focusing on the changes that occur to them depending on their position in the word. Then, this interest expanded to include the basic structure of the word. The non-Arabic origin of a letter is evident through differences in its pronunciation as well as the meanings it conveys. As for the changes in pronunciation, these emerged through the criteria set by the Arabs to identify the non-Arabic origin of a word and how Arab linguists determined the letters they did not pronounce. The words that  have entered Arabic from other languages were found to be subject to change and exhibited a consistent pattern of alterations, including deletion, addition, or phonetic changes. These changes were categorized as  an evidence of the foreign origin of the word, as well as methods for the Arabicization of foreign terms.     In the phonological aspect, we observe that the articulation of sounds in some languages changes, and the pronunciation of these sounds becomes closer to the new borrowed language until the two languages reach complete conformity or are closely aligned in the form of the dominant language     Scholars have observed that the beginning of linguistic evolution in any language starts with phonetic changes as the characteristics of sounds begin to shift into other qualities. This leads to the creation of new sounds and the fading or extinction of older sounds that used to exist.    To understand the use of phoneme pronunciation shifts from one language to another in identifying phonetic borrowing, we will study the phonological changes in Aramaic and some other languages, specifically in comparison with Arabic and some other Northwest and East Semitic languages.
Keywords: Aramaic of the Old Testament, phonetics, Loanwords, similarity